2022
DOI: 10.1063/5.0095106
|View full text |Cite
|
Sign up to set email alerts
|

Different photocurrent response of Cs4PbBr6 particles

Abstract: Zero-dimensional (0D) all-inorganic cesium lead halide perovskites, particularly Cs4PbBr6, have been attracting wide attention due to their excellent optical properties and stability. The research also focuses on the origin of green emission from Cs4PbBr6 which has a bandgap located at UVB region. From now on, both Cs4PbBr6 without visible emission and with green emission have been successfully prepared, however, the origin of green emission remains controversial. Photocurrent response is one of the effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Metal halide perovskites are widely explored in photodetection applications. , The charge carrier generation under illumination leads to positive photoconductivity in these materials. A lot of reports demonstrate the PPC in perovskite materials. Recently, the NPC was reported in halide perovskites under certain conditions. In this line, Yuan et al presented the NPC under illumination in Cs 4 PbBr 6 perovskite single crystals . A significant amount of reduction was observed in the current under illumination than in the dark current.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Metal halide perovskites are widely explored in photodetection applications. , The charge carrier generation under illumination leads to positive photoconductivity in these materials. A lot of reports demonstrate the PPC in perovskite materials. Recently, the NPC was reported in halide perovskites under certain conditions. In this line, Yuan et al presented the NPC under illumination in Cs 4 PbBr 6 perovskite single crystals . A significant amount of reduction was observed in the current under illumination than in the dark current.…”
mentioning
confidence: 99%
“…As we discussed in the above sections that NPC was widely observed in various types of materials. ,,,, Different origin has been proposed for NPC generation, which can be suitable for various kind of applications. The NPC effect has been used for the fabrication of humidity and light sensors, highly sensitive photodetectors, and nonvolatile memories. , Qin et al demonstrated that the NPC in nanodiamonds can be applied for humidity sensors with the sensitivity of 1.26 × 10 6 %, which is the highest in carbon-based humidity sensors . Zhuang et al showed the application of NPC in humidity sensors with a responsivity of 418.1 μAW –1 (at high humid RH = 90%) .…”
mentioning
confidence: 99%